2019
DOI: 10.3144/expresspolymlett.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Semi-alicyclic polyimides as potential membrane oxygenators: Rheological implications on film processing, morphology and blood compatibility

Abstract: Two polyimide structures were prepared from an alicyclic dianhydride and aromatic diamines, containing or lacking fluorine, and were tested as potential membrane oxygenators. First, the solution rheological properties were investigated to evaluate their effect on film processing by tape casting. Velocity and shear rates profiles were simulated to determine the shearing conditions during tape casting and transfer them in the flow curves. Proper films were obtained at a viscosity corresponding to a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The phase images of 134F were obtained with tapping mode at room temperature (Figure ). Figure showed that 134F has an irregular topography, and it consists of a small nodular structure in agreement with similar studies in the literature …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The phase images of 134F were obtained with tapping mode at room temperature (Figure ). Figure showed that 134F has an irregular topography, and it consists of a small nodular structure in agreement with similar studies in the literature …”
Section: Resultssupporting
confidence: 92%
“…Figure 8 showed that 134F has an irregular topography, and it consists of a small nodular structure in agreement with similar studies in the literature. 32 SEM Analysis. SEM analysis of the polymers is an efficient and versatile instrument to clarify the surface morphology of polymers and this analysis provides the details of surface morphology.…”
Section: Reflectance Spectra Of Poly(azomethine-imide)smentioning
confidence: 99%
“…Such a PI molecular design approach produces disruption of the CTC interactions and hence renders better solubility and transparency [14][15][16]. In recent works, we showed that the use of cycloaliphatic dianhydrides in the PI synthesis leads to transparent materials, with high glass transition temperature, good dimensional stability, and appropriate adhesion with the LCs [9,[17][18][19][20][21]. Moreover, such partially aliphatic PIs have a smooth surface and their morphology can be modified by dynamic plowing lithography [22], rubbing [9,11,23], or by imprinting the banded texture of a lyotropic polymer [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Similar dependencies of rheological moduli on shear frequency were reported for other PI structures, revealing a transition from viscous to elastic flow. 32,33 The fc parameter is linked to the relaxation features of the studied polymer fluids, indicating the rate at which the macromolecular structure is changed as a result of the applied variable shearing.…”
Section: Introductionmentioning
confidence: 99%